ANALISIS PERDAGANGAN INTRA-INDUSTRI INDONESIA TERHADAP MITRA DAGANG ASEAN-4 DAN ASIA TIMUR (Studi Kasus : Pada Sektor Manufaktur Tahun 2010-2015) - Debora Angelia Purba (Jurnal Ilmiah Mahasiswa FEB, 2016)
The objective of this research is to find out intra-industry trade in manufactures from Indonesia to trading partners ASEAN-4 and East Asia. Indonesia’s intra- industry trade  measurement  to  trading  partners  is  estimated  by  Grubel-Lloyd index and analyzed by panel data approach. This research will take period 2010-2015.  The  estimated  intra-industry trade  indexes demonstrates that there  is a difference integration, that is strong to very strong integration in Thailand, Malaysia, Singapore, Japan and South Korea. While, Philippines and China in medium integration. The result shows the determinants of intra-industry trade including economic scale, demand structure, geographical distance, and exchange rate  have  significant  effect  on  intra-industry trade between  Indonesia  and  its trading partner.Keywords: Intra-industry trade, manufactures.